Serving the new masters – dendritic cells as hosts for stealth intracellular bacteria. (29th July 2013) - Fabrik, Ivo; Härtlova, Anetta; Rehulka, Pavel; Stulik, Jiri
Summary: Dendritic cells (DCs) serve as the primers of adaptive immunity, which is indispensable for the control of the majority of infections. Interestingly, some pathogenic intracellular bacteria can subvert DC function and gain the advantage of an ineffective host immune reaction. This scenario appears to be the case particularly with so‐called stealth pathogens, which are the causative agents of several under‐diagnosed chronic diseases. However, there is no consensus how less explored stealth bacteria like Coxiella, Brucella and Francisella cross‐talk with DCs. Therefore, the aim of this review was to explore the issue and to summarize the current knowledge regarding the interaction of above mentioned pathogens with DCs as crucial hosts from an infection strategy view. Evidence indicates that infected DCs are not sufficiently activated, do not undergo maturation and do not produce expected proinflammatory cytokines. In some cases, the infected DCs even display immunosuppressive behaviour that may be directly linked to the induction of tolerogenicity favouring pathogen survival and persistence.